Technological mapping of the species Anacardium occidentale: Prospective analysis in Brazil and in the world (Research, Society and Development, 2022)
Anacardium occidentale L., popularly known as Cajueiro, is a species native to Brazil, which has great socioeconomic importance in the Northeast, in addition to medicinal potential described in the literature such as antimicrobial, antidiarrheal and anti-inflammatory effects. In this work, a technological prospection of Cajueiro was carried out, through the survey of patents deposited until June 2021, in the World Intellectual Property Organization (WIPO), European Patent Office (EPO) and National Institute of Industrial Property (INPI) databases. In WIPO and EPO, the highest numbers of deposits were found, with 97 and 47, respectively, while INPI returned 27 properties. It can be observed that Brazil, China, India and Japan are the largest holders of patents involving the development of research on cashew tree, and that these technological properties are mainly related to the medical and food areas. There was also a decrease in recent years of technologies, demonstrating the need for more studies about the potential of the species.